Impairment of tissue repair in pneumonia due to β-cell deficiency: role of endoplasmic reticulum stress in alveolar macrophages - Yamashita, Yoshiro (BMC Res Notes, 2019)
OBJECTIVE: Diabetes mellitus (DM) patients are susceptible to delayed resolution of pneumonia. However, the pathogenesis of the impaired tissue repair in inflamed lungs in diabetic patients is unknown. We evaluated phagocytosis of apoptotic cells (efferocytosis), hepatocyte growth factor (HGF) production in bronchoalveolar lavage fluid (BALF), and lung histology in the resolution phase following acute lung injury in streptozotocin (STZ)-induced β-cell-depleted hyperglycemic mice. We also investigated efferocytosis and HGF production by macrophages under β-cell depletion condition ex vivo. RESULTS: In β-cell-depleted mice, efferocytosis was not significantly different from that in control mice; however, the concentration of HGF in BALF was decreased. In addition, diminished HGF production by alveolar macrophages and DNA synthesis in the alveolar epithelium was observed by immunohistochemistry. Ex vivo experiments confirmed that HGF production by macrophages was impaired under β-cell depletion probably because of endoplasmic reticulum stress. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-019-4209-0) contains supplementary material, which is available to authorized users.